A secure IoT management architecture based on Information-Centric Networking. (March 2016) - Suarez, Javier; Quevedo, Jose; Vidal, Ivan; Corujo, Daniel; Garcia-Reinoso, Jaime; Aguiar, Rui L.
Abstract: This paper explores the use of Information-Centric Networking (ICN) to support management operations in IoT deployments, presenting the design of a flexible architecture that allows the appropriate operation of IoT devices within a delimited ICN network domain. Our architecture has been designed with special consideration to naming, interoperation, security and energy-efficiency requirements. We theoretically assess the communication overhead introduced by the security procedures of our solution, both at IoT devices and clients. Additionally, we show the potential of our architecture to accommodate enhanced management applications, focusing on a specific use case, i.e. an information freshness service level agreement application. Finally, we present a proof-of-concept implementation of our architecture over an Arduino board, and we use it to carry out a set of experiments that validate the feasibility of our solution.